In vitro degradation of self‐reinforced poly(lactic acid) with beta‐tricalcium phosphate composite prepared by equal channel angular pressing. Issue 10 (24th July 2020) - Li, Hong; Xue, Feng; Bai, Jing; Bai, Xiaomin; Ye, Wei; Zhang, Linna; He, Qingsong; Ju, Jia; Ding, Hongyan
Abstract: Poly(lactic acid) (PLA) and beta‐tricalcium phosphate (β‐TCP) are biodegradable biomaterials that can be used in the field of bone fixation. This article aims to investigate the effect of equal channel angular pressing (ECAP) on the mechanical property, physical properties and in vitro degradation behaviors of PLA/β‐TCP (0, 10, and 20 wt%) composites. The bending strength of PLA, PLA/10TCP, and PLA/20TCP composites processed by ECAP were 158, 154, and 137 MPa, respectively, which is higher than its initial samples by 62.8%, 32.7%, and 55.6%. The degradation experiment was carried out in Sorensen's phosphate‐buffered solution at 37°C for 24 weeks. The weight loss rate of PLA/β‐TCP composites processed by ECAP increased fastly but its mechanical property decreased slowly in contrast with hot‐pressed samples. With the degradation proceeding, the existence of β‐TCP resulted in the formation of whisker‐like hydroxyapatite on the surface of PLA/10TCP and PLA/20TCP composites. The oriented fiber structure of PLA matrix disappeared and its internal structure became loose after soaking for 24 weeks. The fiber structure of the PLA/β‐TCP composites formed in the process of ECAP not only increased the initial strength and the degradation rate, but also maintained the mechanical property of the samples in the degradation process. In the meanwhile, the existence of β‐TCP could inhibit the degradation of PLA matrix composites. This study on the in vitro degradation of self‐reinforced PLA/β‐TCP composites prepared by ECAP will provide theoretical support for the development of bone fixation.